Examining the risks of social networking adoption in the Bhutanese healthcare system - Peldon, P.; Issa, Tomayess (Inderscience Publishers, 2015)
Social networking studies have largely focused on opportunities of using it; this study examines the risks of adopting social networking (SN) in the healthcare system in Bhutan. Based on the current literature review, SN use will enhance communication, collaboration, connection, coordination and knowledge sharing among the healthcare professionals and patients, while security, privacy concerns and data accuracy are considered as the main obstacles to social networking adoption. This study employed the qualitative method and the online survey was distributed and collected among the healthcare system in Bhutan. A valid sample size of 145 survey responses was collected giving a response rate of 92.7%. The finding provides insight of the risk the healthcare professionals of Bhutan by adopting social network in the healthcare system. Two new risks generated from this study are security threat and potential implications.